Sistema de ejercicios físicos para el desarrollo de la resistencia aeróbica en futbolistas de la Categoría Sub 14 del Club Formativo Especializado Paris Vinces - Martínez Vega, Jose Vicente (2025)
The purpose of this study is to establish a physical exercise system that contributes to the development of aerobic endurance in U-14 soccer players from the specialized training club Paris Vinces. Aerobic endurance is a fundamental quality for athletic performance, as it allows for sustained effort, improving performance on the field, and preventing injuries. The research is framed within a qualitative approach, utilizing techniques such as surveys and aerobic endurance tests to assess the initial physical conditions of a purposive sample of 16 young soccer players. This methodology will identify the athletes' specific needs and lay the groundwork for designing an exercise system tailored to their characteristics and goals. The final product will consist of a structured training system, based on scientific principles and modern techniques, which will include cardiovascular, muscle strengthening, and active recovery exercises. The implementation of this system is expected to not only improve the soccer players' physical condition but also contribute to their competitive performance and overall development. The research has a significant potential impact on the athletic preparation of the U-14 age group, highlighting the importance of a systematic and personalized approach to aerobic endurance training during the formative stages of football.